Analisis Keanekaragaman dan Kelimpahan Fitoplankton di Sungai Rawas, Sumatra Selatan - Ulpa, Mardiyah; Ihsan, Mahya; Suprayogi, Dawam (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
The Rawas River, a tributary of the Musi River in South Sumatra, faces water quality challenges due to various anthropogenic activities such as household waste, industrial discharge, and agricultural runoff. This study aimed to analyze the diversity and abundance of phytoplankton, as well as water parameters, in the Rawas River. Sampling was conducted at three stations from March to June 2023. Phytoplankton identification was performed in the laboratory using a trinocular microscope, and data analysis included diversity index (H’), evenness index (E), dominance index (C), and PCA analysis. Results identified 49 phytoplankton species across 7 classes, with Bacillariophyceae dominating (69.86%). Station II exhibited the highest diversity (H’ = 3.601) due to effective industrial waste management through IPAL, while Station I showed the highest abundance (37.59%) due to household waste input. PCA analysis identified nitrate, phosphate, water transparency, and current velocity as dominant parameters influencing phytoplankton distribution. This study underscores the importance of waste management in maintaining water quality and preserving the Rawas River ecosystem. Keywords: Phytoplankton, Diversity, Abundance, Rawas River, South Sumatra